2021
DOI: 10.1016/j.asmr.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

High Return to Play Rate and Reduced Career Longevity Following Surgical Management of Athletic Pubalgia in National Basketball Association Players

Abstract: Purpose: To assess the effects of surgical treatment of athletic pubalgia (AP) on game use and performance metrics in National Basketball Association (NBA) players. Methods: A retrospective review of all NBA players who underwent surgical management for AP from 1996 to 2018 was performed. A matched control group was created for comparison. The index period was defined as the entire NBA season in which surgery occurred, including the corresponding offseason. Player demographics, use (games played, games started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Although surgery should most often be considered once conservative treatment has failed, our study adds to the current literature potentially supporting earlier surgical intervention as a viable option in high-level athletes who rely upon their sport as their primary source of income [ 2 , 6 , 7 , 11 , 15 , 16 ]. The results of this study identified a high RTP rate among MLS players (96.5%) who underwent isolated surgical repair of AP.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although surgery should most often be considered once conservative treatment has failed, our study adds to the current literature potentially supporting earlier surgical intervention as a viable option in high-level athletes who rely upon their sport as their primary source of income [ 2 , 6 , 7 , 11 , 15 , 16 ]. The results of this study identified a high RTP rate among MLS players (96.5%) who underwent isolated surgical repair of AP.…”
Section: Discussionmentioning
confidence: 89%
“…Due to the public nature of the data, IRB approval was not needed. Similar to previous studies evaluating RTP statistics in professional athletics, available injury reports, team news articles, individual player timelines, and game statistics were accessed through affiliated team websites (mlssoccer.com and transfermarkt.us) [11][12][13]. Two separate injury reports or articles were considered sufficient for player inclusion in preliminary data collection.…”
Section: Methodsmentioning
confidence: 99%
“…1,13,19,22,23,36,37,40 Although AP surgery is associated with a high return-to-play rate, those who undergo AP surgery are more likely to have a shortened playing career. 4 By identifying risk factors for the development of AP, athletic programs may consider tailoring these modifiable factors to possibly mitigate injury. Recognition and a better understanding of this injury may increase the opportunity for athletes to enjoy healthy, successful careers.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to the transmission control process set in Figure 4 , the sawtooth numerical model was called to fix the multi-level difference generated in the control process ( Castle et al, 2021 ). In the set of multi-level transmission mechanism, corresponding to the protocol followed by the multi-level transmission process ( Beynnon et al, 2020 ; Seow et al, 2020 ), the information fusion processing of sports on mental health status recognition is realized according to the index parameters such as maximum oxygen uptake VO2max and heart rate HR, as shown in Figure 5 .…”
Section: Realize the Recognition And Analysis Of Sports On Mental Hea...mentioning
confidence: 99%